Evaluation of Index of Cardio-Electrophysiological Balance in Patients With Atrial Fibrillation on Antiarrhythmic-Drug Therapy (vol 12, pg 37, 2021) - Afsin, Abdulmecit; Asoglu, Ramazan; Kobat, Mehmet Ali; Asoglu, Emin; Suner, Arif (Elmer Press Inc, 2021)
[Abstract Not Available]